Dostoevsky in English and Shakespearean Universality: A Cautionary Tale - Thurman, Chris (Multicultural Shakespeare: Translation, Appropriation and Performance, 2020)
This is the second of a pair of articles addressing the relationship between Dostoevsky’s novella Notes from the Underground and Shakespeare’s Hamlet. The first article considered the similarities between the two texts, using David Magarshack’s 1968 English translation of the Notes, before discussing the wider phenomenon of Hamletism in nineteenth-century Russia. In this article, the author focuses on the problem of translation, identifying a handful of instances in the Magarshack translation that directly ‘insert’ Shakespeare, and Hamlet in particular, into Dostoevsky’s text. It is argued that these allusions or citations overdetermine the English reader’s experience of Shakespeare-and-Dostoevsky, or Shakespeare-in-Dostoevsky. Returning to the question of Shakespeare’s status in Europe in the nineteenth century, the article concludes with a critique of Shakespearean ‘universality’ as it manifests through the nuances of translation.